The influence of isothermal ageing and subsequent hydrogen charging at room temperature on local mechanical properties and fracture characteristics of martensitic-bainitic weldments for power engineering - Falat L.; Čiripová L.; Homolova V.; Kroupa A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The present study deals with the effects of high temperature expositions and subsequent cathodic hydrogen charging of dissimilar martensitic/bainitic weldment on its local mechanical properties and fracture behaviour at room temperature. Circumferential welded joint under investigation was produced by tungsten inert gas welding of X10CrWMoVNb9-2 martensitic and 7CrMoVTiB10-10 bainitic steels tubes with Ni-based filler metal and the application of subcritical postweld heat treatment. Hardness profile measurements revealed pronounced hardness peaks in over-heated regions of the individual steels heat-affected zones which remained preserved also during subsequent expositions at 600°C for up to 5000 hours. Gradual microstructural degradation of these regions included precipitate coarsening and the formation of new secondary phases during thermal exposure. The combined effects of thermal and hydrogen embrittlement of the studied weldment resulted in deleterious effects on its tensile and fracture behaviour.